PEMETAAN POTENSI DAN UPAYA PELESTARIAN KERAJINAN ANYAMAN BAMBU KHAS DESA SAMARANG KECAMATAN SAMARANG KABUPATEN GARUT - Dewi, Anggraeni Purnama; Rachmat, Ani; Citraresmana, Elvi; Rijati Wardiani, Sri; Sundari Som, Witakania (Unpad Press, 2026)
This article is based on a Community Service conducted in Samarang Village, Samarang District, Garut Regency in June 2026. This village is known as one of the center of traditional bamboo weaving, a craft that has been preserved to the present day, featuring signature products such as boboko (rice baskets), tolombong (deep baskets), nyiru (winnowing trays), aseupan (steaming cones), as well as other household and agricultural tools. This activity aims to document the cultural and economic potential of the weaving craft, identify the challenges faced by artisans in the field, and formulate practical recommendations that can be implemented collaboratively. The methods employed include direct observation of the production process, in-depth interviews, and participatory discussions. The results indicate that while Samarang Village's bamboo crafts possess high quality and cultural value, they face threats from declining demand due to competition from modern products, limited product innovation and marketing capacity, and a lack of interest among the younger generation to continue the tradition. This activity is expected to serve as a foundation for artisans and relevant stakeholders in developing strategic measures for cultural preservation and local economic empowerment. Keywords: Resource Potential; Cultural Preservation; Bamboo Craft; Samarang Garut Village; Local Economy.